2017
DOI: 10.3390/md15040088
|View full text |Cite
|
Sign up to set email alerts
|

Marine Peptides as Potential Agents for the Management of Type 2 Diabetes Mellitus—A Prospect

Abstract: An increasing prevalence of diabetes is known as a main risk for human health in the last future worldwide. There is limited evidence on the potential management of type 2 diabetes mellitus using bioactive peptides from marine organisms, besides from milk and beans. We summarized here recent advances in our understanding of the regulation of glucose metabolism using bioactive peptides from natural proteins, including regulation of insulin-regulated glucose metabolism, such as protection and reparation of pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 121 publications
(142 reference statements)
0
27
0
2
Order By: Relevance
“…These include direct stimulation of pancreatic cells to secrete insulin, inhibition of metabolic enzymes such as dipeptidyl peptidase IV (DPP-IV) and α-glucosidase which are involved in the regulation of serum glucose, stimulation of secretion of incretins (i.e., glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1)) [244]. Many bioactive peptides with antidiabetic potency have been isolated from microalgal and fish protein hydrolysates (Table 4) [211,245,246]. Bioactive peptides with potent inhibition of DPP-IV have specific peptide motifs that consist an N-terminal Trp and/or a Pro at position 2 [245].…”
Section: Antioxidantmentioning
confidence: 99%
“…These include direct stimulation of pancreatic cells to secrete insulin, inhibition of metabolic enzymes such as dipeptidyl peptidase IV (DPP-IV) and α-glucosidase which are involved in the regulation of serum glucose, stimulation of secretion of incretins (i.e., glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1)) [244]. Many bioactive peptides with antidiabetic potency have been isolated from microalgal and fish protein hydrolysates (Table 4) [211,245,246]. Bioactive peptides with potent inhibition of DPP-IV have specific peptide motifs that consist an N-terminal Trp and/or a Pro at position 2 [245].…”
Section: Antioxidantmentioning
confidence: 99%
“…Whereas, the type 2 diabetic patients are insulin resistant, which associates with a decrease in glucose uptake and increase in endogenic hepatic glucose production, thus leading to a hyperglycemic situation [26]. Especially, bioactive agents, which can stimulate glucose uptake, play an important role in the reduction of hyperglycemia in type 2 diabetic patients [27]. In this study, glucose uptake capacity of MIL extract was examined by using LO-2 cells as an in vitro model ( Figure 3).…”
Section: The Effect Mil Extract On Glucose Uptakementioning
confidence: 99%
“…Recently, researchers found that there was an inverse relationship between amount of secretory adiponectin, known as an insulin sensitizer, and the percentage of adipose tissue in the internal organs (Xia et al, 2017). The decreased fat accumulation may improve glucose tolerance by the enhancement of insulin sensitivity (Kwon, Daily, Kim, & Park, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are more than 63 processing units, which generate about 800 tons of octopus by-products (GIPP, 2013). Although numerous studies have been conducted in vivo to demonstrate the anti-hyperglycemic (Harnedy et al, 2018;Xia et al, 2017) and anti-hyperlipidemic (Ktari et al, 2017;Chevrier et al, 2015;Ben Khaled et al, 2012) effects from marine protein hydrolysates, biopeptides from octopus protein hydrolysates in reducing lipid and blood glucose levels still remain unknown.…”
Section: Introductionmentioning
confidence: 99%